INO80 Chromatin Remodeler Facilitates Release of RNA Polymerase II from Chromatin for Ubiquitin-Mediated Proteasomal Degradation - Lafon, Anne (Mol Cell, 2015)
Stalling of RNA Polymerase II (RNAPII) on chromatin during transcriptional stress results in polyubiquitination and degradation of the largest subunit of RNAPII, Rpb1, by the ubiquitin proteasome system (UPS). Here, we report that the ATP-dependent chromatin remodeling complex INO80 is required for turnover of chromatin-bound RNAPII in yeast. INO80 interacts physically and functionally with Cdc48/p97/VCP, a component of UPS required for degradation of RNAPII. Cells lacking INO80 are defective in Rpb1 degradation and accumulate tightly bound ubiquitinated Rpb1 on chromatin. INO80 forms a ternary complex with RNAPII and Cdc48 and targets Rpb1 primed for degradation. The function of INO80 in RNAPII turnover is required for cell growth and survival during genotoxic stress. Our results identify INO80 as a bona fide component of the proteolytic pathway for RNAPII degradation and suggest that INO80 nucleosome remodeling activity promotes the dissociation of ubiquitinated Rpb1 from chromatin to protect the integrity of the genome.